Why does a phosphonium-phosphinate ionic liquid protect the contact surfaces from wear and micropitting but increase vibration when used as an additive in rolling-sliding lubrication?. (July 2021) - Roy, Sougata; Stump, Benjamin C.; Luo, Huimin; Leonard, Donovan; Qu, Jun
Abstract: A phosphonium-phosphinate ionic liquid (IL) was studied as a lubricant additive for rolling-sliding contacts. The bench-scale test was designed to simulate automotive rear axle operation during cold start, highway towing, and overload conditions. Adding such an IL (2%) into a base oil significantly reduced wear loss and rolling contact fatigue, e.g., microcracking and micropitting, but made the vibrational noise notably higher under a low (−1.5%) sliding roll ratio (SRR). Worn surface characterization revealed an interesting texture pattern with alternating smoother plateaus and rougher valleys, which is believed to cause the high vibration. No increased vibration was observed at a high (−30%) SRR, possibly because the more aggressive sliding abrasion prevented such a surface texture from forming. Highlights: Unexpected behavior for a phosphonium phosphinate ionic liquid (IL) in rolling-sliding contact. This IL provided effective wear and rolling contact fatigue protection but increased vibration. Texture of alternating smoother plateaus and rougher valleys responsible for the high vibration.